Pronouns in the Cely Letters - Rutkowska, Hanna (Wydawnictwo Naukowe UAM, 1999)
This paper is a pilot study which makes part of my doctoral project. The paper aims at outlining the pronominal system in selected letters of the Cely family. The main aim of the analysis is the identification of specific morphological categories in the pronominal system in the letters under consideration. Due attention is also paid to the orthographic variants of all the pronouns identified in the corpus.
Keywords: zaimki osobowe; personal pronouns; korespondencja rodziny Cely; Cely Letters; pisownia; spelling